Colibactin leads to a bacteria-specific mutation pattern and self-inflicted DNA damage - Lowry, Emily; Wang, Yiqing; Dagan, Tal; Mitchell, Amir

(untitled) (Genome Research, 2024)
Colibactin produced primarily by Escherichia coli strains of the B2 phylogroup cross-links DNA and can promote colon cancer in human hosts. Here, we investigate the toxin's impact on colibactin producers and on bacteria cocultured with producing cells. Using genome-wide genetic screens and mutation accumulation experiments, we uncover the cellular pathways that mitigate colibactin damage and reveal the specific mutations it induces. We discover that although colibactin targets A/T-rich motifs, as observed in human colon cells, it induces a bacteria-unique mutation pattern. Based on this pattern, we predict that long-term colibactin exposure will culminate in a genomic bias in trinucleotide composition. We test this prediction by analyzing thousands of E. coli genomes and find that colibactin-producing strains indeed show the predicted skewness in trinucleotide composition. Our work reveals a bacteria-specific mutation pattern and suggests that the resistance protein encoded on the colibactin pathogenicity island is insufficient in preventing self-inflicted DNA damage.